Illumina Sequencing and Metabolomics Analysis Reveal Thiamine Modulation of Ruminal Microbiota and Metabolome Characteristics in Goats Fed a High-Concentrate Diet - Ma, Yi; Wang, Chao; Zhang, Hao; Yu, Lihuai; Dong, Li; Gong, Daoqing; Yao, Junhu; Wang, Hongrong (Frontiers in Microbiology, 2021)
Long-term supplementation of a high concentrate diet enhances the accumulation of lactate and decrease in pH in goat rumen, thereby disrupting the composition of microbial community. Studies have shown that incorporation of thiamine in high concentrate diet increases ruminal pH and decreases rumen lactate concentration. To explore the effects of thiamine supplementation with high concentrate diet on altering in whole ruminal microbiota and their metabolites, 18 mid-lactating Saanen goats were randomly fed with one of three diets: (1) control diet (CON; n = 6; concentrate: forage 30:70), (2) high-concentrate diet (HG; n = 6; concentrate: forage 70:30), and (3) high-concentrate diet with 200 mg of thiamine/kg of DMI (HGT; n = 6; concentrate: forage 70:30). The goats received experimental diets for 8 weeks. Ruminal samples were collected on the last day 8 weeks for 16S rRNA Gene Sequencing and the liquid chromatograph-mass spectrometer (LC-MS) analysis. The results revealed significant alterations of ruminal bacterial community structure and diversity in HGT groups compared to HG groups, with an overall dominance of Bacteroidetes at phylum level and Oribacterium (P<0.05), Anaerobiospirillum (P<0.01) and Fibrobacter (P<0.01) at genus level in the HGT group. The LC-MS analysis revealed that thiamine supplementation resulted in lower levels of propionate (P<0.05), pyruvate (P<0.01), lactate (P<0.05), putrescine (P<0.05), tyramine (P<0.05), histamine (P<0.01) and higher levels of acetate (P<0.05), succinates (P<0.01), Oxaloacetic acid (P<0.01), Leucine (P<0.01), Valine (P<0.05), Linoleic acid (P<0.05), Docosahexaenoic Acid (P<0.05), 4-Phenylbutyric acid (P<0.05) in HGT group than in HG group. The decrease in these compounds enhanced homeostasis in the rumen environment and suppressed epithelial inflammation. Correlation analysis revealed the potential relationships between ruminal metabolites and microbial community. These findings demonstrate that thiamine supplementation can alleviate SARA by stabilizing microbial community and reducing toxic unnatural compounds.